Strategi Guru dalam Membimbing Hafalan Do’a Sholat pada Anak Usia Dini di RA Muslimat NU 10 Banin Banat Manyar Gresik - Vivian Liftianah; Ilun Muallifah (Inovasi Pendidikan dan Anak Usia Dini, 2026)
This study examines the teacher's strategy in guiding the memorization of prayer prayers in early childhood at RA Muslimat NU Banin Banat Manyar through a qualitative case study approach. The main focus is the application of the practice (repetition) and habituation method, which was observed for 6-8 weeks in 35 children in group AB (aged 4-6 years), including participant observation, in-depth interviews with 4 teachers and 5 parents, and analysis of RPP documentation and murojaah videos. The results show that the practice method is applied rhythmically daily (3x / day, 10-15 minutes), starting from simple pronunciations such as iftitah and ruku' with 20-30 repetitions per chain cycle, resulting in an average increase in memorization from 42% to 91%, with variations in singing and movements reducing boredom by 27%. Meanwhile, integrated habituation through congregational prayer routines (Dhuha, Zuhur simulation, Ashar), independent ablution, and home supervision, achieved 89% of children's independence in becoming mini imams after 21 days consistently, supported by verbal rewards and gender row rotation. The discussion confirmed alignment with Piaget's theory (preoperational stage) and Vygotsky's (ZPD scaffolding), where drills build sensory memory schemes while habituation forms permanent religious character ala Abdullah Nasih Ulwan. Supporting factors include parental collaboration and a conducive NU environment, overcoming the obstacle of low concentration. Practical implications recommend replicating this strategy in similar RAs to optimize the golden age of Islamic early childhood, with memorization retention of 8-10 basic prayer prayers.